Design and Evaluation of a Failure Detection Algorithm for Large Scale Ad Hoc Networks Using Cluster Based Approach - Mohan Khilar, P.; Kumar Singh, J.; Mahapatra, S. (11th International Conference on Information Technology : ICIT 2008 : proceedings : December 17-20, 2008, Bhubaneswar, India, 2008)
In this paper we propose a scalable failure detection service for large scale ad hoc networks using an efficient cluster based communication architecture. Our failure detection service adapts the detection parameter to the current load of the wireless ad hoc network. The proposed approach uses a heartbeat based testing mechanism to detect failure in each cluster and take the advantage of cluster based architecture to forward the failure report to other cluster and their respective members. The simulation results show that this approach is linearly scalable in terms of message complexity and consensus time.